PENDIDIKAN KARAKTER PADA ANAK USIA SD OLEH ORANG TUA DI RW 004 KELURAHAN SUNGAI BERINGIN KECAMATAN TEMBILAHAN KABUPATEN INDRAGIRI HILIR - Kanoer, Lia Wahyuni Kanoer Wahyuni; Maemunaty, Titi Maemunaty; ', Widiastuti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract:This research is motivated by moral decline nations childern , it is mainly visible in the RW 004 Sungai Beringin Vilage Tembilahan district, Indragiri Hilir. The formulation of this research is whather the character education at elementay school age children by parents in the RW 004 Sungai beringin of Tembilahan district, Indragiri Hilir regency of classified good. The aim of this research is to know the supporting how well the character education at elementary school age childeren by parents in the RW 004 Sungai Beringin Vilage of Tembilahan district, Indragiri Hilir regency. The population of this research is 65 people. The technique used in this research Probability sampling and the sampling method is using simple random sampling, researchers conducted random sampling using Slovin formula with a critical level of 10%, in order to obtain a sample of 39 people. The data instrument is 62 questionnaire. The data is analyzed with quantitative descriptive analysis. From the analysis of data can be in the know that character education at elementary school age children by people in RW 004 Sungai Beringin Vilage of Tembilahan district, Indragiri Hilir regency classified as very good. Keywords: Character Education At elementary school age children by perents